The Women of Uganda Network (Uganda) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Women of Uganda Network (WOUGNET) is an NGO established in 2000 to promote the use of ICTs for sharing information and addressing issues collectively.